Microgels formed by electrostatic complexation of gelatin and OSA starch: Potential fat or starch mimetics. (May 2015) - Wu, Bi-cheng; McClements, David Julian
Abstract: The creation of high quality reduced-calorie food products is challenging because the removal of digestible fats or carbohydrates compromises quality attributes. The aim of this research was to create hydrogel microspheres from gelatin and octenyl succinic anhydride (OSA) modified starch for potential use as fat droplet or starch granule mimetics. Hydrogel microspheres were formed based on the ability of cationic gelatin and anionic OSA-starch to phase separate through electrostatic complexation. Mixtures of type A gelatin (0.5 wt%) and OSA-starch (0–2.0 wt%) were dispersed in water at room temperature. Upon acidification to pH 5, the mixtures formed molecular complexes due to electrostatic attraction between gelatin and OSA-starch. The influence of polymer ratio on the formation of the molecular complexes was determined by micro-electrophoresis and turbidity analysis. Static light scattering and microscopy revealed that spindle to oval shaped particles were formed with a mean diameter (d3, 2 ) ranging from around 5 to 13 μm with the maximum particle size being achieved at 0.5% gelatin and 0.4 wt% OSA-starch. These particles may be useful as texture modifiers or to encapsulate lipophilic molecules to improve the sensory quality of reduced calorie products. Graphical abstract: Hydrogel particles can be formed through electrostatic complexation of gelatin and OSA starch. The microstructure of the hydrogel particles can be regulated by controlling the electrostatic interaction between gelatin and OSA starch. These hydrogel particles may be used as fat or starch mimetics to modify texture of food products and/or to encapsulate functional ingredients. Highlights: Electrostatic complexation of gelatin and modified (OSA) starch was studied. Complex formation depended on gelatin-to-OSA-starch ratio and solution pH. Hydrogel particles of different morphology could be formed by regulating conditions. These hydrogel particles may be used as fat or starch mimetics or as delivery systems.